(untitled) (Research, Society and Development, 2022)
With the accelerated growth process of cities, it becomes essential to think about the ways in which the urban space should develop, especially regarding its territorial planning, use and occupation of the land. In this sense, we can mention the creation and implementation of territorial planning plans that stand out as tools for guidance and construction of these spaces and seek, through a careful and technical look, to contribute to the emergence of cohesive, compact and planned cities. In view of this, the present study sought, using geographic information systems, to map and evaluate the effects of the new Teresina Territorial Planning Plan - PDOT - (Law 5.481/2019) on the potential for occupation and urban expansion. Applying the technique of Procedural Hierarchical Analysis (AHP) the standardization and organization of the geographic data deemed relevant and that directly influence the decision process regarding the occupation and use of the land was conducted. To determine the data values, weights were assigned, according to degrees of importance, in a weight matrix from which the Consistency Index (CI) and the Consistency Ratio (RC) were determined for validation of the AHP. Considering the results obtained, it has been effectively observed that the new PDOT has promoted changes in land use and occupation, as well as in the way the city grows. Thus, many areas that could be occupied were identified, however with reservations and restrictions of an environmental nature and a strong tendency towards cohesion and compaction of the city.